The Understanding of Religious and Multicultural Culture in Manado City Society from Maqâshid al-Syarî`ah Perspective - Rizal Darwis; Abdullah Abdullah; Nazar Husain Hadi Pranata Wibawa; Arhjayati Rahim (Jurnal Madania, 2022)
Religion and culture are two inseparable things. Grounded religious values require traditions and culture that develop in society. This article aims to analyze the religious and cultural understanding of multiculturalism in the people of Manado City. This research is a qualitative descriptive study with data sources coming from the literature and interviews. The data were analyzed using the maqâshid al-syarî`ah approach. The results of the study show that the city of Manado as an area with a multicultural population strongly adheres to the religious understanding that every religion in principle loves, respects, and respects each other. The philosophy of sitou timou tumou tou, torang samua basudara, mapalus, democracy, anti-discrimination and friendship are believed and guided in carrying out all social activities in Manado society. If viewed from the perspective of maqâshid al-syarî`ah, then it is included in the category of maslahat al-‘ummah.